Coordination and metalation bifunctionality of Cu with 5,10,15,20-tetra(4- pyridyl)porphyrin: Toward a mixed-valence two-dimensional coordination network - Li, Yang; Xiao, Jie; Shubina, Tatyana; Chen, Min; Shi, Ziliang; Schmid, Martin; Steinrück, Hans-Peter; Gottfried, J. Michael; Lin, Nian (Journal of the American Chemical Society, 2012)
We investigated the coordination self-assembly and metalation reaction of Cu with 5,10,15,20-tetra(4-pyridyl)porphyrin (2HTPyP) on a Au(111) surface by means of scanning tunneling microscopy, X-ray photoelectron spectroscopy, and density functional theory calculations. 2HTPyP was found to interact with Cu through both the peripheral pyridyl groups and the porphyrin core. Pairs of pyridyl groups from neighboring molecules coordinate Cu(0) atoms, which leads to the formation of a supramolecular metal-organic coordination network. The network formation occurs at room temperature; annealing at 450 K enhances the process. The interaction of Cu with the porphyrin core is more complex. At room temperature, formation of an initial complex Cu(0)-2HTPyP is observed. Annealing at 450 K activates an intramolecular redox reaction, by which the coordinated Cu(0) is oxidized to Cu(II) and the complex Cu(II)TPyP is formed. The coordination network consists then of Cu(II) complexes linked by Cu(0) atoms; that is, it represents a mixed-valence two-dimensional coordination network consisting of an ordered array of Cu(II) and Cu(0) centers. Above 520 K, the network degrades and the Cu atoms in the linking positions diffuse into the substrate, while the Cu(II)TPyP complexes form a close-packed structure that is stabilized by weak intermolecular interactions. Density functional theory investigations show that the reaction with Cu(0) proceeds via formation of an initial complex between metal atom and porphyrin followed by formation of Cu(II) porphyrin within the course of the reaction. The activation barrier of the rate limiting step was found to be 24-37 kcal mol depending on the method used. In addition, linear coordination of a Cu atom by two CuTPyP molecules is favorable according to gas-phase calculations. © 2012 American Chemical Society.